Geochemistry and organofacies characteristics of organic-rich chalky marl deposits, northern Jordan: Insights into Type II-S source rock - Hakimi, M.H. (Elsevier Ltd, 2022)
This study deals with organic matter in chalky marls of the Wadi Shallala Formation in northern Jordan. We report geochemical analyses (Total organic carbon, programmed pyrolysis, bitumen extraction, and pyrolysisâgas chromatography) for the chalky marls from 17 samples to provide information on the quantity, quality, the thermal maturity of the organic matter, their potential as petroleum source rocks. The chalky marl samples contain a significant amount of total organic carbon (TOC, max = 6.53) and hydrogen index (HI) ranging from 300 to 702 mg HC/g TOC. The organic facies are mainly Types-II and -I kerogen with a potential to generate high amounts of oil. The dominance of such kerogen is consistent with significant amounts of fluorescent alginite macerals, observed under ultraviolet light microscopy. These organic facies are also confirmed by the Py-GC investigation, showing sulfur-rich Type II-S kerogen. The presence of weak carbonâsulfur (C-S) bounds in the kerogen molecules, however, suggests the generation of sulfur-rich oil at the early stages during the oil-generation window as reported by earlier works. Both geochemical maturity indicators (i.e., Tmax and PI) and the fluorescence color of the liptinite macerals indicate that the studied chalky marls in the outcropped section of the study area are still thermally immature, and maturity did not alter the organic-rich intervals to generate suitable oil for commercial production. Therefore, these organic-rich sediments in the locations having relatively deeper stratigraphic sections are likely to be promising source rocks and recommend for petroleum exploration and production in northern Jordan. Â© 2021 Elsevier Ltd